Cecal Microbiota Modulates Fat Deposition in Muscovy Ducks - Lyu, Wentao; Liu, Xiuting; Lu, Lizhi; Dai, Bing; Wang, Wen; Yang, Hua; Xiao, Yingping (Frontiers in Veterinary Science, 2021)
Ducks with the same genetic background vary greatly in their adiposity phenotypes. The gut microbiota plays an essential role in host physiological development and metabolism including fat deposition. However, the association of the gut microbiota with the lipogenic phenotype of ducks remains unknown. In this study, we investigated the cecal microbiota of adult Muscovy ducks and the correlation of the cecal microbiota with fat phenotypes. A total of 200 Muscovy ducks were selected from a population of 5000 Muscovy ducks to record their abdominal fat weight and collect their cecal contents after being slaughtered and defeathered. The cecal contents were subjective to DNA isolation and 16S rRNA gene sequencing. The results were sorted according to the percentage of abdominal fat and the top 20% (n = 40) and the bottom 20% (n = 40) were set as the high and low groups, respectively. Our results indicated that in the cecum of Muscovy ducks, Bacteroidetes, Firmicutes, and Fusobacteria were the predominant phyla while Bacteroides, Oscillospiraceae_uncultured, Parabacteroides, and Bacteroidales_norank were the top 4 dominant genera. Abdominal fat weight (18.57~138.10 g) and percentage of abdominal fat (1.02~27.12%) were significantly correlated (R2 = 0.92, P < 0.001). Although the lipogenic phenotypes of ducks had a significant difference (P < 0.05), the α-diversities of the high and low groups were not significantly different (P > 0.05). Nevertheless, after random forest analysis, we identified two genera, Treponema and Ruminococcus_torques_group, that were significantly associated with fat deposition in Muscovy ducks. In addition, the abundances of Treponema and Ruminococcus_torques_group gave a significantly negative and positive association with abdominal fat weight, respectively (P < 0.05). Ducks with a low level of Treponema exhibited a tendency toward a high percentage of abdominal fat (P < 0.01), while the percentage of abdominal fat in ducks with high Ruminococcus_torques_group abundance tended to be higher than that in ducks with low Ruminococcus_torques_group abundance (P < 0.01). These findings could provide the basic data on the cecal microbiota in Muscovy ducks as well as a theoretical foundation to limit the fat deposition by modulating the gut microbiota in the duck industry.